PLANNING OF HEAVY EQUIPMENT REQUIREMENT IN EXCAVATION AND SOIL MANAGEMENT WORK (CASE STUDY : MEDICAL BUILDING CONSTRUCTION PROJECT PHASE 2 OF SITI KHODIJAH MUHAMMADIYAH HOSPITAL ALONG BRANCH) - Ummah, Nisfu Fajarayana Khoiro; Sarya, Gede (Jurnal Teknik Sipil, 2023)
Earthwork on the Medical Building Construction Project Phase 2 of Siti Khodijah Muhammadiyah Hospital Along Branch is one of the main keys to withstand the building's resilience structure. This Building Construction Project has obstacles to the ongoing excavation and Mgrading work, tools that need to be improved, and less supportive terrain conditions. As a result, the completion of work may be delayed leading to cost overruns. Therefore, the need for an active role of management, especially productivity calculations, to determine fundamental change steps so that these obstacles can be avoided or reduced. To analyze the machine's productivity, it must be by the theory of machine productivity related to the subject matter obtained and the appropriate stages of analysis. Thus, machine planning must be carried out carefully and precisely so that the effectiveness of optimal machine use and time can be achieved by calculating the productivity value of the machine. Based on the data analysis, the results of heavy equipment needs were obtained, namely, two units of excavated excavators, five units of dump trucks, and two units of Mgrading excavators. With the total costs incurred to complete the excavation and Mgrading work, namely for excavators Rp. 124,785,550.00 and dump trucks Rp. 11,496,875.00. To complete the excavation and Mgrading work takes 205 hours excavator and 13 hours dump truck.